A new find of Megalotragus priscus (Alcelaphini, Bovidae) from the central Karoo, South Africa - Brink, J. S.; de Bruiyn, H.; Rademeyer, L. B.; van der Westhuizen, W. A. (Bernard Price Institute for Palaeontological Research, 1995)
We document the occurrence of the Florisian, or late Quaternary, form of the giant alcelaphine, Megalotragus priscus, from dongas on the Ongers River, near Britstown in the central Karoo. This is significant as it confirms the occurrence of the species in the Karoo and it suggests significantly wetter environments and productive grasslands in the central Karoo in pre-Holocene times. The present-day Karoo environment did not maintain populations of large ruminant grazers similar to M. priscus, and other specialized Florisian grazers, prior to the advent of agriculture and pasture management. Aridification in recent times is the likely cause of changes in grassland quality and the local dissappearance of these animals, if not their extinction.
Main article
Keywords: A1celaphine evolution, Florisian mammals, Late Pleistocene extinction